2002
DOI: 10.1046/j.1471-0528.2002.02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Active management of term prelabour rupture of membranes with oral misoprostol

Abstract: Objective To compare the active management of term prelabour rupture of membranes with oral misoprostol with conservative management for 24 hours followed by induction with oxytocin or prostaglandin E 2 (PGE 2 ) gel. Design A non-blinded randomised controlled trial.Setting Induction and labour wards, Aberdeen Maternity Hospital.Population Sixty-one women with confirmed prelabour rupture of the membranes at ! 36 weeks of gestation.Methods The women were randomised to 50 Ag of oral misoprostol repeated every 4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…In 1996, Ngai et al [47] investigated the effectiveness of oral misoprostol as a cervical-priming agent for patients presenting with prelabor rupture of membranes at term and suggested that oral misoprostol is an effective agent for this group of patients. Similar results were published by Sanchez-Ramos et al [27] in 1997 and Shetty et al [48] in 2002. The latter concluded that active management with oral misoprostol resulted in more women going into labor and delivering within 24 h of prelabor rupture of membranes with no increase in maternal or neonatal complications.…”
Section: Labor Induction At Termsupporting
confidence: 88%
“…In 1996, Ngai et al [47] investigated the effectiveness of oral misoprostol as a cervical-priming agent for patients presenting with prelabor rupture of membranes at term and suggested that oral misoprostol is an effective agent for this group of patients. Similar results were published by Sanchez-Ramos et al [27] in 1997 and Shetty et al [48] in 2002. The latter concluded that active management with oral misoprostol resulted in more women going into labor and delivering within 24 h of prelabor rupture of membranes with no increase in maternal or neonatal complications.…”
Section: Labor Induction At Termsupporting
confidence: 88%
“…These studies are summarized in Table 3. 18,20,[28][29][30][31][32][33][34][35][36][37][38] In 1996, the first documented study of oral misoprostol use for women with PROM evaluated a 200 mcg dose for cervical ripening compared to placebo prior to administration of oxytocin for induction of labor. 28 Improvements in Bishop score (8.4 vs 5.0; 95% CI, 2.2-4.1; P Ͻ .05), lower rates of oxytocin use (13% vs 51%; 95% CI, 2.2-4.1; P Ͻ .001), and a shorter interval from PROM to birth (7.5 [6.0] vs 16.2 [3.9]; 95% CI, 6.1-11.3; P Ͻ .01) were noted.…”
Section: Management Of Prelabor Rupture Of Membranes With Orally Admimentioning
confidence: 99%
“…This study showed a longer interval from induction to birth in the misoprostol group (720 min [382] vs 501 min [389]; P = .007), equal rates of maternal satisfaction, and no differences in rates of uterine tachysystole or maternal or neonatal outcomes. 29 In a study by Shetty et al (2002), women with PROM (N = 61) were treated with orally administered misoprostol every 4 hours, up to 5 doses, followed by oxytocin if necessary; or expectant management up to 24 hours, followed by application of vaginally administered prostaglandin E2 gel if women had an unfavorable cervix; or oxytocin with a favorable cervix if not already in active labor. When uterine contractility suggested active labor for women receiving oral misoprostol, a sterile vaginal examination was performed and the women were transferred to the labor ward for management of labor or oxytocin augmentation, as indicated.…”
Section: Management Of Prelabor Rupture Of Membranes With Orally Admimentioning
confidence: 99%
See 1 more Smart Citation
“…Active induction of labor soon after PROM reduces the risks of maternal and foetal sepsis 4 compared with conservative management, and is associated with a shorter interval from PROM to significant uterine contractions and delivery. 6 For the labour that is induced, the timing of the induction is controversial. Indeed, the decision to induce labour often depends more on the convenience of the physicians, nurses or midwives than on the actual time that elapsed after rupture of the membranes.…”
Section: Introductionmentioning
confidence: 99%